Implementation of Notary Cooperation with Banks in Making Fiduciary Guarantee Deeds (Case Study: PT. BPR Bumi Sediaguna, Tegal Regency) - Proborini, Jessica Refi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The role of a notary very important in helping to create certainty and legal protection for the community, because a notary as public official authorized to make an authentic deed, the implementation of the notarial deed, one of them is a guarantee of the fiduciary over to the notary telepas bank did not.But in practice in melakasanakan business it, always had difficulty in making the deed fiduciary security.The purpose of the research is to analyze: 1) Implementation of cooperation with the notary in making the deed in pt fiduciary security.Earth sediaguna district tegal BPR. 2) Obstacles and solutions in the implementation of cooperation with the notary in making the deed in pt fiduciary security.Earth sediaguna district tegal BPR. The approach method in this study is an approach to legislation (state approach).This type of research includes the scope of normality empirical legal research.Type and data sources in this study are primary data and secondary data obtained research on library or libraryl research and field research.The analysis in this study is descriptive. Research concluded: 1). A fiduciary agreement stated in a notary deed called a fiduciary bail deed.Confirmation of fiduciary security agreements was made with a notary deed by attaching debit documents related to fiduciary security binding.Credit agreements made with fiduciary guarantees are not legal guarantees., but it appears because there is a need for contracts between banks as creditors and customers as debitors.Legal function of binding fiduciary objects in fiduciary bail certificates cannot be separated from credit agreements.But in practice often the received documents are incomplete, This led to delays in the creation of fiduciary bail certificates. 2) Obstacle and solution in implementing notary cooperation with the bank in creating fiduciary bail certificate in pt.Bpr Earth is used. The moor district is often incomplete on banks. Input data into credit agreements.